Antimicrobial activity and pH measurement of calcium silicate cements versus new bioactive resin composite restorative material - Ashraf Abou ElReash; Hamdi Hamama; Waleed Eldars; Gong Lingwei; Ahmed M. Zaen El-Din; Xie Xiaoli (BMC, 2019)
Abstract Background The purpose of this in vitro study is to compare the antimicrobial effect and pH of two calcium silicate cements Mineral trioxide aggregate high plasticity (Angelus PR, Brazil) and iRoot BP Plus (BioCeramix Inc., Vancouver, BC, Canada) and new bioactive restorative resin composite restorative material (ACTIVA, MA, Pulpdent, USA) against aerobic bacteria, strictly anaerobic bacteria and a yeast by using an agar diffusion test. Methods The materials were tested immediately after manipulation and were applied to the agar plates. Sodium hypochlorite (NaOCl) 5.25% was used as a positive control group. The dry filter paper acted as a negative control group for this study. The size of the inhibition zone for each material was measured after 12, 24 and 48 h. At the time of pH measurement; materials were prepared, crushed then dispersed in distilled water. Results The one-way Anova test revealed that iRoot BP Plus significantly showed superior antimicrobial efficacy compared to MTA-HP against the following species; Staphylococcus aureus, Streptococcus mutans, Enterococcus faecalis, Enterococcus faecium, Peptostreptococcus anaerobius and Candida albicans (P < 0.05). All of the tested materials did not show any antimicrobial effect against Porphyromonas gingivalis and Actinomyces israelii. The new bioactive resin composite material (ACTIVA) showed the least antimicrobial activity against the previously mentioned microorganisms except E. faecalis. NaOCl significantly showed the highest antimicrobial activity among the test group (P < 0.05). iRoot BP Plus was more alkaline (pH 12.1 ± 0.14/ 11.9 ± 0.25) in comparison to MTA-HP (pH 11.6 ± 0.16/ 11.2 ± 0.10) while ACTIVA was slightly acidic (pH 5.4 ± 0.09/ 6.5 ± 0.08). Conclusions According to the findings of this study, it was concluded that calcium silicate- based cements showed a potential antimicrobial activity mainly due to its high alkalinity. The new bioactive resin composite restorative material exhibits less antimicrobial activity due to its resinous ingredients and slightly acidic nature. Antimicrobial effect of calcium silicate cements against strictly anaerobic bacterial species is still questionable.